2018
DOI: 10.1016/j.cub.2018.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Wing Motor Control of Song and Flight

Abstract: Multifunctional motor systems produce distinct output patterns that are dependent on behavioral context, posing a challenge to underlying neuronal control. Flies use their wings for flight and the production of a patterned acoustic signal, the male courtship song, employing in both cases a small set of wing muscles and corresponding motor neurons. We took first steps toward elucidating the neuronal control mechanisms of this multifunctional motor system by live imaging of muscle ensemble activity patterns duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 62 publications
9
100
0
Order By: Relevance
“…Given the diverse neuronal morphologies within the ensemble of Tdc2-Gal4 neurons (Busch et al, 2009;Claßen and Scholz, 2018) , it seems highly unlikely that all OA neurons function as a single 'mega-interneuron'. Indeed, recent work has shown that, depending on experimental parameters, activation of Tdc2 neurons can decrease song behaviors (O'Sullivan et al, 2018) or promote male-to-male courtship (Certel et al, 2007) , demonstrating the functional diversity of Tdc2 neurons and OA action. The extent to which hierarchical OA activation is mediated by either spatial effects via the recruitment of different Tdc2-Gal4 cell types and distribution of different OA receptor types, or by superposed effects by behavioral state and odor within individual neurons, requires further investigation.…”
Section: Octopaminergic Neuromodulation Of Visual Processing Is Hieramentioning
confidence: 99%
“…Given the diverse neuronal morphologies within the ensemble of Tdc2-Gal4 neurons (Busch et al, 2009;Claßen and Scholz, 2018) , it seems highly unlikely that all OA neurons function as a single 'mega-interneuron'. Indeed, recent work has shown that, depending on experimental parameters, activation of Tdc2 neurons can decrease song behaviors (O'Sullivan et al, 2018) or promote male-to-male courtship (Certel et al, 2007) , demonstrating the functional diversity of Tdc2 neurons and OA action. The extent to which hierarchical OA activation is mediated by either spatial effects via the recruitment of different Tdc2-Gal4 cell types and distribution of different OA receptor types, or by superposed effects by behavioral state and odor within individual neurons, requires further investigation.…”
Section: Octopaminergic Neuromodulation Of Visual Processing Is Hieramentioning
confidence: 99%
“…Connectomic reconstruction was previously undertaken for a larval Drosophila nervous system (Ohyama et al, 2015;Schneider-Mizell et al, 2016) and an adult brain (Takemura et al, 2013;Tobin et al, 2017;Zheng et al, 2018), but not yet for an adult VNC, which accounts for a third of the adult central nervous system and contains all limb motor neurons. A VNC connectome would enhance our understanding of how VNC circuits control muscles of the legs (Soler et al, 2004), neck (Strausfeld et al, 1987), wings (O'Sullivan et al, 2018), and halteres (Dickerson et al, 2019) to give rise to complex behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…There is precedent for this hypothesis, as hg1 is one of four control wing muscles (hg1-4) that insert into a common tendon that influences the mechanical properties of the posterior notal wing process at the wing hinge (Fig. 1); moreover, all four hg muscles are active during D. melanogaster courtship song (O'Sullivan et al, 2018). Given the potential functional overlap among the hg muscles, loss of the size dimorphism in hg1 may have been associated with a compensatory gain of a size dimorphism in another hg wing muscle, or vice versa.…”
Section: Sexual Size Dimorphisms In the Drosophila Wing Musculature Amentioning
confidence: 99%
“…1) based on the sclerite into which they insert (i.e., basalare, first and third pterale, and the posterior notal wing process). How the control wing muscles influence the generation of Drosophila song has been investigated most thoroughly in Drosophila (D.) melanogaster (Ewing, 1977;Ewing, 1979;Shirangi, Stern & Truman, 2013;O'Sullivan et al, 2018). The song of D. melanogaster males consists of trains of pulses and bouts of continuous tone called pulse song and sine song, respectively.…”
Section: Introductionmentioning
confidence: 99%